2016
DOI: 10.1111/1475-6765.12172
|View full text |Cite
|
Sign up to set email alerts
|

Institutional veto players and cabinet formation: The veto control hypothesis reconsidered

Abstract: Are potential cabinets more likely to form when they control institutional veto players such as symmetric second chambers or minority vetoes? Existing evidence for a causal effect of veto control has been weak. This article presents evidence for this effect on the basis of conditional and mixed logit analyses of government formations in 21 parliamentary and semi‐presidential democracies between 1955 and 2012. It also shows that the size of the effect varies systematically across political‐institutional context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
0
18
0
1
Order By: Relevance
“…Flexibility Duration-weighted average of cabinet types, based on the following ranking: 0 = majority cabinet .5 = formal minority cabinet 1 = substantial minority cabinet Values reflect the house with greater overall flexibility in the period under consideration. Strøm (1990) and Döring and Manow (2016) for lower houses, Eppner and Ganghof (2017) for upper houses, own data collection based on case-specific sources.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flexibility Duration-weighted average of cabinet types, based on the following ranking: 0 = majority cabinet .5 = formal minority cabinet 1 = substantial minority cabinet Values reflect the house with greater overall flexibility in the period under consideration. Strøm (1990) and Döring and Manow (2016) for lower houses, Eppner and Ganghof (2017) for upper houses, own data collection based on case-specific sources.…”
Section: Resultsmentioning
confidence: 99%
“…It thus lacks the power and legitimacy to change the overall character of democracy, even when its electoral system differs substantially from that of the lower house. On the other hand, if a directly elected upper house can also dismiss the cabinet in a no-confidence vote, it is likely to become too powerful (see Eppner and Ganghof 2017). If the composition between the two chambers -the two principals of the cabinet -differs substantially, parliamentarism and bicameralism get into conflict, so that the institutional configuration is unlikely to be stable in the long-run.…”
mentioning
confidence: 99%
“…In particular, Lijphart (1984Lijphart ( , 1987Lijphart ( , 1999 conjectured that cabinet builders tend to form oversized coalitions in order to control strong second chambers (see also Sjölin, 1993). More recently, it has been found that those government coalitions holding a majority of seats in each chamber are more likely to form (Druckman et al, 2005;Eppner and Ganghof, 2017) and have a substantially longer life (Druckman and Thies, 2002) in comparison to those that do not control the upper chamber. As previously noted, however, this literature has primarily focused on the institutional prerogatives of the two chambersthat is, on the degree of symmetry in the powers of the two houses.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Operationalisierung: Effektive Anzahl der Dimensionen, basierende auf den Ergebnissen einer Hauptkomponentenanalyse. Dabei werden Parteipositionen auf ver- Datenquellen: Strøm (1990) sowie Döring und Manow (2016) für Unterhäuser, Eppner und Ganghof (2017) für Oberhäuser; ergänzt durch eigene Datensammlung.…”
Section: Dimensionalitätunclassified